1997
DOI: 10.1016/s0304-3959(97)00015-8
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar transplants of immortalized serotonergic neurons alleviate chronic neuropathic pain

Abstract: The RN46A cell line was derived from embryonic day 13 rat medullary raphe cells by infection with a retrovirus encoding the temperature-sensitive mutant of SV40 large T antigen. This cell line is neuronally restricted and constitutively differentiates following a shift to non-permissive temperature. Brain-derived neurotrophic factor (BDNF) induced the serotonergic phenotype and increased the survival of RN46A cells in vitro. After transfection of the rat BDNF gene into RN46A cells, an autocrine BDNF-secreting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 66 publications
2
34
0
1
Order By: Relevance
“…Compelling evidence has demonstrated that the overexpression of BDNF is essential for development of neuropathic pain and inflammatory pain (Siuciak et al, 1994(Siuciak et al, , 1995Eaton et al, 1997;Thompson et al, 1999;Kerr et al, 1999;Mannion et al, 1999;Cejas et al, 2000;Deng et al, 2000;Ramer et al, 2000;Obata et al, 2003;Coull et al, 2005;Hayashida et al, 2008;Miletic and Miletic, 2008;Trang et al, 2009;Yang et al, 2009;Zhou et al, 2009;Geng et al, 2010;Valdes-Sanchez et al, 2010). We also show that i.t.…”
Section: Discussionsupporting
confidence: 62%
“…Compelling evidence has demonstrated that the overexpression of BDNF is essential for development of neuropathic pain and inflammatory pain (Siuciak et al, 1994(Siuciak et al, , 1995Eaton et al, 1997;Thompson et al, 1999;Kerr et al, 1999;Mannion et al, 1999;Cejas et al, 2000;Deng et al, 2000;Ramer et al, 2000;Obata et al, 2003;Coull et al, 2005;Hayashida et al, 2008;Miletic and Miletic, 2008;Trang et al, 2009;Yang et al, 2009;Zhou et al, 2009;Geng et al, 2010;Valdes-Sanchez et al, 2010). We also show that i.t.…”
Section: Discussionsupporting
confidence: 62%
“…BDNF has also been demonstrated to increase 5HT synthesis in raphe neurons in vitro by increasing expression of tryptophan hydroxylase (TPH; the rate-limiting enzyme for 5HT synthesis). 52 Lumbar subarachnoid grafts of cells that synthesized both BDNF and 5HT were able to reverse chronic neuropathic pain after CCI, 53 and neuropathic pain after dorsal hemisection injury of the spinal cord. 54,55 Serotonergic inhibition of primary afferents, 56 individual spinal neurons, 57 as well as the presence of ascending serotonergic sensory pathways, 58 suggest that changes in the serotonergic systems might facilitate or inhibit the development of chronic pain after PNS and CNS injury.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to alter BDNF levels with chronic delivery of exogenous neurotrophic factors, such as BDNF to the CNS, is problematic as they will not cross the blood-brain barrier and must be directly injected or chronically infused. Chronic delivery of BDNF 69 and 5HT 53,54 from subdurally grafted bioengineered neuronal cells, functioning as cellular minipumps, resulted in an attenuation of the altered sensory behaviors in neuropathic pain. These findings suggest that a chronic source of BDNF alone might directly affect the reversal of those behaviors after partial nerve injury.…”
Section: With a Similar Injection Of A Control Raav-gfp Vector (Greenmentioning
confidence: 99%
“…In fact, animals could be left 20 min on the plate with no signs of injury. 29 To further ensure that this protocol did not cause tissue injury, immediately after 5 min on the 5Ā°C plate we assessed the surface temperature of the hind paws with an infrared thermometer (Fisher Scientificā„¢ Traceableā„¢ Noncontact Infrared Thermometers) in rats (n = 9) and mice (n = 6).…”
Section: Methodsmentioning
confidence: 99%